Hubungan Usia Kehamilan dan Paritas dengan Kejadian Infeksi Saluran Kemih Pada Masa Kehamilan di Wilayah Kerja Puskesmas Pante Raya Kecamatan Wih Pesam Kabupaten Bener Meriah Provinsi Aceh Tahun 2023 - Evalina Evalina; Siska Suci Triana Ginting; Herly Herly; Junida Laia (NAJ Nursing Applied Journal, 2024)
Background: Maternal health is a measure of the level of social welfare. Maternal death is the death of a woman during pregnancy, childbirth or within 42 days after the end of pregnancy. Perineal rupture is the second most common cause of postpartum bleeding. Tearing may coincide with uterine atony. Based on data from the World Health Organization (WHO), 2.7 million cases of perineal rupture occurred in mothers giving birth. This figure is estimated to reach 6.3 million in 2050. One way to prevent perineal rupture is to maintain the elasticity of the perineum. Increasing the elasticity of the perineum is done by means of pregnancy exercises. The aim of this study was to determine the relationship between pregnancy exercise and perineal rupture in postpartum mothers at Anemia Of Pregnant Women At BPM Helena Astuti Sinaga. The research design is an analytical study with a cross-sectional approach. The population in this study was all mothers giving birth at Anemia Of Pregnant Women At BPM Helena Astuti Sinaga in November-March 2023, namely 764 people with a research sample of 88 people. The sampling technique used random sampling and research analysis used the chi square test. The research results showed that the majority of pregnant women who took part in pregnancy exercise at BPM were 47 (53.4%) and those who did not do pregnancy exercise were 41 (46.6%). Inpartum mothers who experienced perineal rupture were 42 (47.3%) and those who did not experience perineal rupture were 46 (52.3%). Based on the results of statistical tests between pregnancy exercise and perineal rupture, the p value = 0.003 (p < 0.05). The conclusion of this study is that there is a significant relationship between pregnancy exercise and perineal rupture during birth at BPM Helena Astuti Sinaga. So it was suggested to Anemia Of Pregnant Women At BPM Helena Astuti Sinaga to improve services, especially for pregnant women, to do pregnancy exercises.